Fitness for full-contact fighters : training for muay thai, kick-boxing, karate, and taekwondo - Delp, Christoph, 1974- (Berekeley, Calif. : Frog, Ltd., 2006)
'An indispensable fitness training guide for all martial artists helping them to optimise their ability to perform through the development of flexibility, stamina, and power'--Provided by publisher
Includes bibliographical references
Keywords: Martial arts -- Training